Pengaruh Kepercayaan Dan Komitmen Terhadap Kualitas Hubungan Dampaknya Pada Kinerja Rantai Pasokan (Studi Kasus Produksidan Distribusi Dedak Pada PD Sederhana) - Moh. Mukhsin (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
The purposes of this study is to determine whether there is influence of Trustand Commitment to Supply Chain Performance with Quality of Relation asan interveningvariable, Production and Distribution case study of Dedak on PD. Sederhana. Variablesused in this research are trust and commitment as independent variables, Supply ChainPerformance as Dependent variable, and quality of relation as intervening variable. Thisresearch used quantitative method by using descriptive research and causal research. Datafrom the 4 variables were analyzed by using Structural Equation Model (SEM) inSoftware SmartPLS (Partial Least Square) version 1.0. The numberof samples used in thisstudy were 57 respondents.Based on the result of data analysis, it can be concluded thatthere is positive and significant relation among trust and commitment to the quality ofrelation, whereas there is positif significant relationamong Trust and commitment tosupply chain performance. The result of analysis indicate that the quality of relation is ableto mediate trust and commitment influence to supply chain performance.